Patent foramen ovale diagnosis: The importance of provocative maneuvers. Issue 1 (22nd July 2016) - Mongodi, Silvia; Via, Gabriele; Riccardi, Mariachiara; Tavazzi, Guido; D'Armini, Andrea Maria; Maurelli, Marco; Braschi, Antonio; Mojoli, Francesco
ABSTRACT: Patent foramen ovale (PFO) is a frequent congenital anomaly, but massive right‐to‐left shunt (RTLS) is normally prevented by higher pressures in left heart chambers. However, mechanical ventilation with positive end‐expiratory pressure (PEEP) can significantly increase right atrial pressure, accentuating the RTLS, mainly after major cardiothoracic surgery. We report a patient admitted to the intensive care unit after cardiac surgery. Pre‐ and intraoperative transesophageal echocardiography only described an aneurysmal interatrial septum with no shunt. However, high‐PEEP ventilation induced a paradoxical response with life‐threatening hypoxemia, triggering further echocardiographic evaluation, revealing massive RTLS across a stretch PFO. Provocative maneuvers (Valsalva/PEEP) significantly increase echocardiographic sensitivity, unmasking silent PFO. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :58–61, 2017